PERBEDAAN HITUNG JUMLAH TROMBOSIT METODE IMPEDANSI, LANGSUNG DAN BARBARA BROWN - Dewi Ratih Maharani; Herlisa Anggraini; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2017)
The purpose of this research is to know the difference of calculation result of thrombocyte count with Impedance method, Direct and Barbara Brown. This research uses analytical research with cross sectional design. The independent variables are Impedance method, Direct and Barbara Brown. The bound method is the number of platelets. Sampling technique used is quota sample of 8 patients with 3 treatments. The result showed the number of Impedance method thrombocyte with an average value of 241.375 ; Direct with an average value of 240.375 ; Barbara Brown with an average value of 241.250.Based of statistical test of Repeated Anova on difference of Impedance method and Direct got significancy value 0,351 ; Impedance method and Barbara Brown got significancy value 0,909 ; and Direct method and Barbara Brown got significancy value 0,371. Thus it can be concluded that there is no difference in the results of the number of platelets count between the Impedance method, Direct and Barbara Brown Keywords: Number of Platelets, Impedance, Direct, Barbara Brown